Find the non-zero x satisfying ( 2 − 3 ) x + ( 7 − 4 3 ) ( 2 + 3 ) x = 4 ( 2 − 3 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I totally did agree with your solution.. @Rohit Udaiwal .. +1 , but we can minimize the answer by rewriting the 3rd step and then solving further
( 2 − 3 ) x + ( 2 − 3 ) 2 − x = 4 ( 2 − 3 ) ( 2 − 3 ) x − 1 + ( 2 − 3 ) 1 − x = 4 a = ( 2 − 3 ) x − 1 a + a 1 = 4 a 2 − 4 a + 1 = 0 a = 2 4 ± 1 6 − 4 a = 2 ± 3 ( 2 − 3 ) x − 1 = 2 − 3 , 2 − 3 1 x − 1 = 1 or − 1 ⟹ x = 2 or 0
Log in to reply
Better! Upvoted!
Hello Sambhrant!I knew there would be a shorter/clearer method but I didn't bothered to find it;thanks for doing it.I believe you should post this a solution and I myself will upvote it.Great job :)
Just re-posting the solution given by @Sabhrant Sachan
( 2 − 3 ) x + ( 2 − 3 ) 2 − x = 4 ( 2 − 3 ) ( 2 − 3 ) x − 1 + ( 2 − 3 ) 1 − x = 4 a = ( 2 − 3 ) x − 1 a + a 1 = 4 a 2 − 4 a + 1 = 0 a = 2 4 ± 1 6 − 4 a = 2 ± 3 ( 2 − 3 ) x − 1 = 2 − 3 , 2 − 3 1 x − 1 = 1 or − 1 ⟹ x = 2 or 0
Problem Loading...
Note Loading...
Set Loading...
Notice that 2 + 3 1 = 2 − 3 and 7 − 4 3 = ( 2 − 3 ) 2 .Then we have ( 2 − 3 ) x + ( 7 − 4 3 ) ( 2 + 3 ) x ⟹ ( 2 − 3 ) x + ( 2 − 3 ) x 7 − 4 3 ⟹ ( 2 − 3 ) 2 x − 4 ( 2 − 3 ) ( 2 − 3 ) x + 7 − 4 3 ⟹ a 2 − 4 ( 2 − 3 ) a + 7 − 4 3 = 4 ( 2 − 3 ) = 4 ( 2 − 3 ) = 0 [ Multiplying both sides by ( 2 − 3 ) x ] = 0 [ where a = ( 2 − 3 ) x ] The above equation being a quadratic equation,has it roots given by the quadratic formula as a ⟹ a ∴ x = 2 4 ( 2 − 3 ) ± { 4 ( 2 − 3 ) } 2 − 4 ( 7 − 4 3 ) = 2 8 − 4 3 ± ( 2 3 7 − 4 3 ) = 4 − 2 3 ± ( 2 3 − 3 ) [ ∵ ( 7 − 4 3 ) = ( 2 − 3 ) 2 ] = 1 , ( 7 − 4 3 ) ⟹ ( 2 − 3 ) = 1 , ( 2 − 3 ) 2 = 0 , 2
Hence,the only non-zero root is 2 .